2020
DOI: 10.1007/s00198-020-05388-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing patients initiating abaloparatide, teriparatide, or denosumab in a real-world setting: a US linked claims and EMR database analysis

Abstract: We characterized patients initiating abaloparatide (ABL), teriparatide (TPTD), or denosumab (DMAB) in a real-world clinical setting from a large medical and pharmacy claims database. Differences were noted in sex, age, pathologic fractures, comorbidity index, and prior bisphosphonate use for patients initiating ABL and TPTD compared with those receiving DMAB. Introduction To characterize patients initiating abaloparatide (ABL), teriparatide (TPTD), or denosumab (DMAB) treatment in a real-world clinical setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Each patient's study period began up to five years before their initial treatment of apixaban or rivaroxaban (index date), or January 2013, whichever was later; the earliest index date in the study was January 2014. Data were derived from the OM1 Real-World Data Cloud (RWDC), a multi-source, real-world proprietary data network with linked healthcare claims, social determinants, and electronic medical record (EMR) data on patients in the US [20], and a linked dataset on prescribers. All participant and provider data are fully de-identified.…”
Section: Methodsmentioning
confidence: 99%
“…Each patient's study period began up to five years before their initial treatment of apixaban or rivaroxaban (index date), or January 2013, whichever was later; the earliest index date in the study was January 2014. Data were derived from the OM1 Real-World Data Cloud (RWDC), a multi-source, real-world proprietary data network with linked healthcare claims, social determinants, and electronic medical record (EMR) data on patients in the US [20], and a linked dataset on prescribers. All participant and provider data are fully de-identified.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of a large medical and pharmacy claims US database showed that approximatly 12% of patients who received TPTD had a history of glucocorticoid long-term exposure which is double the percentage of patients prescribed Denosumab [ 10 ], indicating a prescriber’s preference for the use of TPTD in GIOP. Most multicentre observational studies have included patients who were concurrently treated with glucocorticoids; however, the frequency of GIOP patients varied from 2.7 to 14.4% (JFOS, ExFOS, EFOS), as outlined in Table 1 .…”
Section: Teriparatide Data In Various Patient Groupsmentioning
confidence: 99%
“…In day-to-day practice TPTD is mostly prescribed to patients with severe osteoporosis who have sustained one or more vertebral fractures or non-vertebral fractures [ 9 ]. In the US a medical claims database analysis of 200 million patients showed that between May 2017 and September 2018 almost 10,000 patients were prescribed TPTD, which would equate to approximately 50 new TPTD patients per million per year [ 10 ], a number which is reflected by a single center cohort study in the UK which included 500 patients over 11.5 years in a health board of approximately 1 million patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%